The Effect of Indonesian Bayleafs [Syzygium polyanthum (Wight.) Walp] Ethanol 70% Extract Granule to the Mortality of Anopheles aconitus Larvae - Muhamad Dwi Heriansyah; Sutartinah Sri Handayani; Novianto Adi Nugroho (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2016)
Introduction: Due to the high rate of malaria incidence in Indonesia and antimalaria drugs resistance causes increment of mortality and morbidity rate for the patients. Most people to cope with the situation, tend to use larvicide to manage the vector but in the process it face some difficulity that not only it can harm the environment but also tend to develop resistance. This research will focus to find an alternative larvicide made by plant to substitute the synthetic larvicide. This research tries to determine the effect of Indonesian bayleaf granule extract to the mortality of Anopheles aconitus larvae. Methods: This research used laboratory experimental design with the post test only control group design. This experiment was used Indonesian Bayleafs [Syzygium polyanthum (Wight.) Walp] granule ethanol extract as larvicide against Anopheles aconitus larvae. Larvae were divided into 9 groups, each group contains 25 larvaes. For the negative control group 100 ml aquadest was used. The other 8 groups which 1 group with 3500 mg dextrin was added, and 7 group with different granule concentration (1700 mg, 2100 mg, 2500 mg, 2900 mg, 3300 mg, 3700 mg, 4100 mg). This research conducted with 4 times replication based on WHO guideline. The observation was held after 24 hours the experiment are conducted, and then the number of dead larvae was counted. The data was analysed with ANOVA, LSD and Probit test. Results: ANOVA test, LSD, was used to analyse the data it showed that there are significant difference of larvae mortality between the experimental group. Probit test that was also used showed that the LC50 is is 2,005.3 mg/100 ml and the LC99 is 7,730.41 mg/100 ml. Conclusion: There was effect of Indonesian bayleaf [Syzygium polyanthum (Wight.) Walp] granule ethanol extract to the mortality of Anopheles aconitus. The LC50 is 2,005.3 mg/100 ml and the LC99 is 7,730.41 mg/100 ml. Keyword: granules, Indonesian bayleaf extract, Anopheles aconitus larvae, mortality